Transgenic overexpression of endogenous FLOWERING LOCUS T-like gene MeFT1 produces early flowering in cassava - Odipio, John; Getu, Beyene; Chauhan, R. D.; Alicai, Titus; Bart, Rebecca; Nusinow, Dmitri A.; Taylor, Nigel J. (PLoS ONE, 2020)
Endogenous FLOWERING LOCUS T homolog MeFT1 was transgenically overexpressed under control of a strong constitutive promoter in cassava cultivar 60444 to determine its role in regulation of flowering and as a potential tool to accelerate cassava breeding. Early profuse flowering was recorded in-vitro in all ten transgenic plant lines recovered, causing eight lines to die within 21 days of culture. The two surviving transgenic plant lines flowered early and profusely commencing as soon as 14 days after establishment in soil in the greenhouse. Both transgenic lines sustained early flowering across the vegetative propagation cycle, with first flowering recorded 30–50 days after planting stakes compared to 90 days for non-transgenic controls. Transgenic plant lines completed five flowering cycles within 200 days in the greenhouse as opposed to twice flowering event in the controls. Constitutive overexpression of MeFT1 generated fully mature male and female flowers and produced a bushy phenotype due to significantly increased flowering-induced branching. Flower induction by MeFT1 overexpression was not graft-transmissible and negatively affected storage root development. Accelerated flowering in transgenic plants was associated with significantly increased mRNA levels of MeFT1 and the three floral meristem identity genes MeAP1, MeLFY and MeSOC1 in shoot apical tissues. These findings imply that MeFT1 encodes flower induction and triggers flowering by recruiting downstream floral meristem identity genes.
Keywords: Transgenic; FLOWERING LOCUS T-like gene MeFT1; Flowering; Cassava